Profound Anatomical and Physiological Changes During Trimesters of Pregnancy. A Clinical Study - Arisha Sana Memon, Abdul Hafeez Baloch, Muhammad Muqeem Mangi, Sadia Iqbal, Hina Mawani, Fakharunissa (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and objectives: Current study was conducted from February 2022 to June 2022 in different Gynecological and medical institutes of Pakistan. The aims and objectives of study were to observe the anatomical and Physiological changes during Pregnancy in women. Materials and Methods: Sample size: 100 pregnant women were selected for this study and their age was in between 25-35 years. It was first pregnancy of all women how were considered in study. Parameters: Cardiac changes, renal vasculature, renal vasodilatation, renal plasma flow and glomerular filtration rate (GFR), respiratory changes, water metabolism, changes in alimentary tract, thyroid changes, blood glucose levels, systolic and diastolic blood pressure. Bio-statistical presentation: Raw data were presented by bio-statistically with the application of SPSS regression model 2020 in which compression was operated through mean standard deviation and significant (P<0.05) variations. Results: It was seen that during pregnancy the demand of oxygen showed a significant (P<0.05) increase (95.0±0.01), this is brought by a 20% rise in oxygen intake and 15% increase in metabolic rate and similarly Systolic blood pressure, Diastolic blood pressure, Random blood glucose levels, Intra-gastric pressure, Heart rate and BMI (152.0±0.03, 92.1±0.01, 156.0±0.01, 95.0±0.00, 9.0±0.02, 93.0±0.01, 35.01±0.01) in pregnant women also showed a significant (P<0.05) changes than the normal levels respectively. Conclusion: Pregnancy brings about physiological and anatomical changes that support the growing fetus and get the mother ready for labor and delivery. It’s critical to distinguish between pathology associated with disease and typical physiological changes.